The Quest for Knowledge in the “King James Bible” - Piotrowska-Oberda, Ewa (Respectus Philologicus, 2014)
The aim of this article is the quest for knowledge in the King James Bible (1611) in terms of quantitative and qualitative research methodology with the application of the statistical analysis tool Antconc. The quest for knowledge with the use of corpus research aims at discussing the Biblical concept of knowledge through the origin, the object of knowledge, its implications and its constant development. Knowledge is often seen as of divine nature, reflected in the soul of man. It is based not only on logical, but also on the spiritual and ethical reasoning. The object of knowledge is light, reflecting the divine nature of knowledge which exceeds the intellect to reach a deeper spiritual human reasoning. In the King James Bible (1611) the authors of New Testament consider human knowledge to be imperfect and partial. They emphasize the need for a spiritual man aiming at reaching a complete knowledge. This spiritual development is based on the relationship between knowledge and faith, as well as knowledge and love. For the authors of the books of the New Testament there is no dichotomy between both knowledge and faith and knowledge and love, because faith and love depend on knowledge that originates in the word of God and leads to spiritual development. From this perspective, religious knowledge, love and mercy as well as faith developed through the knowledge of the biblical text leads to the knowledge of God, the enlightening source of ultimate knowledge. Thus, in the spiritual development of man not only the knowledge and faith but also emotional intelligence, which expresses itself through love and charity as the safer guide in all controversial issues, are important